Building a measurement system of higher education performance: evidence from a Latin-American country (2020)
Purpose: The purpose of this paper aims to propose and validate a measurement scale for integrating performance in universities with a global and local Latin-American perspective. Design/methodology/approach: This research followed a sequential, mixed-method design which uses quantitative and qualitative approaches. The data collection and analysis used two stages. The first stage was a systematic literature review analysing the data through a bibliometric analysis followed by thematic analysis. From this stage emerged the global universities' performance thematic map, a flow diagram for universities' performance system and a measurement scale. The second stage validated this scale applying a survey to the academic and administrative staff members of two Colombian private universities. A total of 705 useable responses were collected and analysed using exploratory factor analysis and the SPSS software. Findings: The results validated five dimensions (research, resources, internationalisation, extension and academics) and 15 indicators proposed to determine the performance in universities. This study concluded that the instrument developed for measuring performance is a consistent starting point for the study of universities in Latin-American countries such as Colombia. Research limitations/implications: This study empirically validated the instrument for measuring performance from a systemic perspective at universities; however, a broader validation of the measurement scale is needed in the context of developing countries in Latin America to generalise the results. Practical implications: Results provide a starting point considering the Latin-American context. They could help in future studies to improve the understanding of performance management in higher education. Originality/value: Performance in universities has created multiple parameters and indicators, generating a lack of global consensus for their measurement. Thereof, this paper contributes to filling this gap in Latin-American universities. This work postulates a starting point considering the local context from global reported findings. It integrated the relations visually for sub-dimension and performance indicators into the university performance system. From this research emerged a novel theoretical hierarchical model for measuring university performance. © 2020, Emerald Publishing Limited.